Leitura em (dis)curso: uma proposta dialógica para análise da obra Peter E Wendy, De J. M. Barrie - Mattos, Luana de Souza (2019)
The present master's dissertation Reading in (dis)course: a dialogical proposition for the analysis of the work Peter and Wendy, by J. M. Barrie analyzed the dialogical construction featured in the mentioned work. A proposition of dialogical analysis started from the assumption that the words do not have a sense in themselves, since they derive from discursive formations in which they are inscribed. In the Bakhtin Circle perspective, discourse is conceived not as an individual speech but as a meaningful instance in which other discourses intertwine and intersect. The voices that inhabit the narrator's discourse in the work Peter and Wendy are thus evidenced, and which, in the Bakhtinian perspective, provided a reading that recognizes the boundaries between the discourse of the self and the other. From a dialogical methodology of analysis, the present work sought to understand the point of contact between language and reality, starting from the idea that the subject of verbal interaction is a social subject, constituted by the social voices that pass through it. The methodological procedures that integrated the analysis device of the corpus were based on the active responsive attitude, the heterodiscourse, the chronotope, the dialogical relationship between the self and the other, the presence of the other in the speech of the self and the multiplicity of voices that emerge from the work analyzed. Therefore, these procedures were used to recognize, through the presence of discourses established by the narrator, the effects of meaning and the ideological resonances that, in fiction, provided the discursivity of the work Peter and Wendy. Thus, from J.M. Barrie's description of English society and family typical of the early twentieth century, the work was able to encounter the emerging voices in the work Peter and Wendy and to understand the social values based on patriarchal society, the importance of the family for the maintenance of this society and the social roles that the characters represent. Therefore, it was possible to conclude that the composition of the work was extremely circumscribed by the historical and cultural context in which it was written, revealing in its narrative the period characteristics of its period, facts of the author's own life and reference works of the construction of his identity literary.